The Man with tow shadows and other ghost stories - Hood, Thomas; Crowe, Catherine; Greenwood, Louise; Hood, Tom; Hopkins, Andy; LE Fanu, Joseph sheridan; Lemon, Mark; Potter, Jocelyn (England, UK Longman pearson, 2008)
"Penguin Readers are simplified texts which provide a step-by-step approach to the joys of reading for pleasure'
Level 3 1200 headwords
Pre-Intermediate
8 12
Keywords: English as a second language; English language -- Pronunciation; English stories; Vocabulary; Word skills